Venous thromboembolism incidence in the Cooperative Study of Sickle Cell Disease. (18th October 2014) - Naik, R. P.; Streiff, M. B.; Haywood, C.; Segal, J. B.; Lanzkron, S.
Summary Background Venous thromboembolism (VTE) has been recently recognized as a complication of sickle cell disease (SCD); however, the incidence of VTE in SCD is unknown. Objectives The primary objective of this study was to determine the incidence of first VTE, including pulmonary embolism (PE) and deep vein thrombosis (DVT), among SCD patients age ≥ 15 years. We also evaluated genotypic differences in VTE risk and determined the relationship between VTE and mortality. Patients/methods In this retrospective cohort study, we used data from the Cooperative Study of Sickle Cell Disease (CSSCD) to calculate incidence rates for first VTE. We used Cox proportional hazard models to estimate hazard ratios (HRs) for time to VTE by genotype and time to death by VTE status. Results We included 1523 SCD patients aged ≥ 15 years with 8862 years of follow‐up in this analysis. The incidence rate for first VTE was 5.2 events/1000 person‐years (95% confidence interval [CI] 3.8–6.9) with a cumulative incidence of 11.3% (95% CI 8.3–15.3) by age 40 years. Individuals with the SS/Sβ0‐thalassemia genotype had the highest rate of VTE (7.6 events/1000 person‐years [95% CI 5.3–10.6]). The incidence of PE exceeded that of isolated DVT (3.6 [95% CI 2.5–5.1] events/1000 person‐years vs. 1.6 [95% CI 0.9–2.7] events/1000 person‐years), although this difference was not statistically significant. SCD patients with VTE had a higher mortality rate (adjusted HR 2.32 [95% CI 1.20–4.46]) than those without VTE. Conclusions Patients with SCD are at substantial risk for VTE, and individuals with VTE are at higher risk of death than those without VTE.